Does human support add value to persuasive design-based digital mental health interventions? A propensity score matching study of a digital parenting program - Saar, Chen R.; Brandes, Or; Baumel, Amit (Frontiers in Digital Health, 2025)
BackgroundWhile human support has been shown to increase user engagement with digital mental health interventions, it also increases managerial overhead, raises costs, and limits scalability. An alternative approach leverages persuasive design principles to potentially reduce the reliance on human support. Therapeutic persuasiveness (TP) is a concept for persuasive design that involves incorporating features that encourage users to make positive behavior changes in their lives. Prior research suggests that TP features can effectively improve both user engagement and intervention outcomes.ObjectiveThis study aimed to evaluate the added value of human support in a TP-enhanced digital parent training program (DPT) by comparing engagement and clinical outcomes between human-supported and self-directed intervention formats.MethodsA propensity score matching approach was used to utilize data from two comparable studies, involving parents of children aged 3–7, all of whom received the same TP-enhanced DPT. One study included a self-directed condition (n = 38), while the other included a human-supported condition (n = 38). Human support was provided via chat and phone calls and included progress acknowledgments, personalized feedback, disengagement follow-up, and timely responses to parent-initiated messages. Engagement patterns and pre-to-post intervention changes in child behavior, parenting practices, and parental self-efficacy were compared between the two intervention formats.ResultsThere were no significant differences between the self-directed and human-supported formats in program completion rates (89% vs. 92%, respectively; P = .51), the percentage of parents completing all the modules (81.6% vs. 76.3, P = .57) or total usage time (137 vs. 141 min, P = .14). Parents in the human-supported version logged in significantly more frequently than those in the self-directed group (Cohen's ds = 0.32, 0.34; Ps ≤ .04), which is attributed to parents’ additional engagement in messaging with the supporter. No significant differences were observed between groups in reported improvements in children's behavior problems, parenting practices, or parental self-efficacy (Ps ≥ .17).ConclusionsThese findings suggest that well-designed, technology-enabled intervention features may effectively support program adherence and therapeutic outcomes without requiring additional human support. This study highlights the importance of further research into the relative impact of human-supported vs. self-directed DMHIs and investigating how intervention quality might influence this impact.